2023
DOI: 10.1038/s12276-023-00927-z
|View full text |Cite
|
Sign up to set email alerts
|

RGS2 promotes estradiol biosynthesis by trophoblasts during human pregnancy

Abstract: Production of estradiol (E2) by the placenta during human pregnancy ensures successful maintenance of placental development and fetal growth by stimulating trophoblast proliferation and the differentiation of cytotrophoblasts into syncytiotrophoblasts. Decreased levels of E2 are closely associated with obstetrical diseases such as preeclampsia (PE) in the clinic. However, the mechanisms underlying the inhibition of placental E2 biosynthesis remain poorly understood. Here, we report that regulator of G-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…ShRNA sequences used are as follows: shRNA sequence targeting ARID1A: 5'-AAC CAA AGT TAC TGT TGT TTA-3'; and a scrambled shRNA sequence (5'-TTT GTA CTA CAC AAA AGT ACTG-3') was used as control. Sequences were obtained from Shanghai Sangon Biotechnology Co. Ltd. Lentiviruses expressing ARID1A-shRNA or scrambled-shRNA were generated by co-transfecting the HEK293T packaging cells with lentiviral shRNA expression vector, and lentiviruses-containing supernatants with the titers greater than 1×10 6 cfu/ml was used for infection of cells in the presence of 8 μ g/ml polybrene (Sigma-Aldrich; Merck KGaA) as previously described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ShRNA sequences used are as follows: shRNA sequence targeting ARID1A: 5'-AAC CAA AGT TAC TGT TGT TTA-3'; and a scrambled shRNA sequence (5'-TTT GTA CTA CAC AAA AGT ACTG-3') was used as control. Sequences were obtained from Shanghai Sangon Biotechnology Co. Ltd. Lentiviruses expressing ARID1A-shRNA or scrambled-shRNA were generated by co-transfecting the HEK293T packaging cells with lentiviral shRNA expression vector, and lentiviruses-containing supernatants with the titers greater than 1×10 6 cfu/ml was used for infection of cells in the presence of 8 μ g/ml polybrene (Sigma-Aldrich; Merck KGaA) as previously described ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from SK-OV-3 cells and A2780 cells by using a TRIzol reagent (Takara Biotechnology Co., Ltd.) according to the manufacturer's instructions. 5 μ g of total RNA was reversely transcribed by using SuperScript III reagent (Thermo Fisher Scientific, Inc.) according to the manufacturer's protocol, and the oligo-(deoxythymidine) primer with incubation at 42°C for 1 h. After the termination of cDNA synthesis, mRNA levels of target genes were determined by RT-qPCR as previously described ( 21 ). Briefly, the initial denaturation was 95°C for 5 min; followed by 40 cycles of denaturation (95°C, 10 sec), annealing and extension (60°C, 30 sec).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, RGS2 promoted protein degradation of HAND1 and restored transcription of HAND1-inhibited aromatase, leading to increased estrogen levels. 73 In addition to the abovementioned hormones, Yu et al 74 identified placensin, a peptide hormone derived from the placenta, which is capable of stimulating glucose secretion and trophoblast invasion. Serum placensin level rises in a stage-dependent manner during pregnancy and is significantly increased in patients with gestational diabetes mellitus during the third trimester.…”
Section: In Humansmentioning
confidence: 99%
“…A recent study showed an uncharacterized role of RGS2 in the production of estrogen by the placenta. Specifically, RGS2 promoted protein degradation of HAND1 and restored transcription of HAND1-inhibited aromatase, leading to increased estrogen levels 73 . In addition to the abovementioned hormones, Yu et al 74 .…”
Section: Recent Progress In Trophoblast Differentiation and Placentat...mentioning
confidence: 99%